The model of degressive taxation of trucks: Case of the Czech Republic - Břetislav Andrlík; Michaela Podlasová (DANUBE: Law, Economics and Social Issues Review, 2021)
The article examines issues related to the design of road tax as an instrument supporting the operation of trucks that are more environment-friendly to the transport infrastructure. The Introduction presents analyses of road taxation in the European Union Member States, whose aim was to identify features supporting trucks that are eco-friendly with regard to the infrastructure. The principal part of the contribution is the formulation of a regression model of road tax rates, which is subjected to statistical, econometric and economic verification in order to confirm or disprove degressivity of road tax rates for trucks. The economic verification is based on typical examples of vehicles defined in Annex 2 to the text. The Conclusion presents the results achieved, which verify the degressive nature of road tax in the Czech Republic. The tax rates are degressive in relation to the number of truck axles; therefore, a proposal for the elimination of degressivity in the system of tax rates for trucks was designed based on the principle of fair taxation, which is also discussed in the contribution.
Keywords: 330; Road Tax; Transport Infrastructure; Degressivity; TruckTax Rate